Implementation of a color system as a strategy for patient safety in a pediatric ICU: experience report (Research, Society and Development, 2021)
Objective: to report the experience of implementing a color identification system to promote patient safety in a Pediatric Oncology Intensive Care Unit of a federal hospital in the city of Rio de Janeiro. Methodology: this is a descriptive research of the experience report type, which was based on the goals 1 and 3 of the World Health Organization. Results: in the implementation process, the colors were systematically distributed, where each bed or unit of the The patient received a corresponding color, as well as related items, such as: medical records, clipboards, medication storage containers, medication identification labels and bottles for administration in an infusion pump. This system was extended to continuous infusion medications according to the degree of complexity (vasoactive amines, sedative analgesia, among others), as well as the identification of infusion pumps, equipment and infusion lines for each drug in progress. Conclusion: the method was performed in order to contribute to the promotion of patient safety, since the use of colors establishes another element for checking and, therefore, a "barrier" strategy inserted in the identification process, whose objective is to minimize adverse events due to human error, in addition to improving the identification practice that already exists in the institution.